Distributing worlds through aesthetic encounters - Stoll, Joshua; Underwood, Brandon; Xiang, Shuchen (Cambridge Scholars Publishing, 2017)
This collection consists of a selection of papers presented at the 2014 Uehiro Cross Currents Philosophy Conference, which focused on comparative philosophy, held at the University of Hawai'i in Mānoa. The annual student conference opens up opportunities for dialogue across cultures and traditions and challenges the status quo of academic philosophy's focus on Western thought alone, as exhibited in this book. Doing so has both aesthetic and political implications. In one way, to the extent that comparative philosophy outlines new possibilities for how the world can be distributed-how things ca.